2020
DOI: 10.1186/s12885-020-07604-8
|View full text |Cite
|
Sign up to set email alerts
|

Shortwave infrared emitting multicolored nanoprobes for biomarker-specific cancer imaging in vivo

Abstract: Background The ability to detect tumor-specific biomarkers in real-time using optical imaging plays a critical role in preclinical studies aimed at evaluating drug safety and treatment response. In this study, we engineered an imaging platform capable of targeting different tumor biomarkers using a multi-colored library of nanoprobes. These probes contain rare-earth elements that emit light in the short-wave infrared (SWIR) wavelength region (900–1700 nm), which exhibits reduced absorption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…SWIR‐emitting nanocomposites have multispectral capabilities based on the RE dopant. [ 22,27 ] Future studies can address the issue of delineating signal from nonspecific binding through multispectral imaging using a mix of differently doped CD8‐targeted and isotype control‐conjugated ReANCs to unravel the actual signal from that of nonspecific uptake through spectral unmixing. [ 50 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…SWIR‐emitting nanocomposites have multispectral capabilities based on the RE dopant. [ 22,27 ] Future studies can address the issue of delineating signal from nonspecific binding through multispectral imaging using a mix of differently doped CD8‐targeted and isotype control‐conjugated ReANCs to unravel the actual signal from that of nonspecific uptake through spectral unmixing. [ 50 ]…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with similar studies that have reported nonlinear relationships between ligand density and target cell binding. [24,27,36] Among the tested CD8-ANCs, those conjugated with a loading density of 28.6 μg IgG mg À1 HSA had the most significant binding effect on CTLs, followed by a loading density of 42.9 μg IgG mg À1 HSA. We selected nanocomposites with the loading density of 28.6 μg IgG mg À1 HSA for all other experiments based on these results.…”
Section: Cd8-targeted Ancs Bind To Cytotoxic T Cells In Vitro With Hi...mentioning
confidence: 99%
See 2 more Smart Citations
“…50,53,54 There is a high volume of research in this area, and multicolor emitters are available. 55,56 Detectors for SWIR wavelengths are often different than those for the red or NIR wavelengths, 57 and so it is feasible to use separated detectors for parallelization or spectral decomposition through a spectrometer. 58,59 Time-gated detection can be coupled with wavelength-based separation of the signals as well, to further maximize the ability to detect signals at the same time, and scintillation-based signals can be orders of magnitude faster than organic fluorescence, which in turn is orders of magnitude faster than phosphorescent signals.…”
Section: Multiplexing Of Signalsmentioning
confidence: 99%